An Analysis of Leading Sectors in Sleman District - Gea Dwi Asmara; Fadli Anggoro Yekti (Universitas Nusantara PGRI Kediri, 2024)
This research endeavors to ascertain the preeminent sectors within Sleman Regency during the timeframe spanning 2018 to 2022. Additionally, the study aims to discern the sectors that constitute the primary focal points for economic development within Sleman Regency, situated in the Yogyakarta Special Region Province. Secondary data, acquired from the Central Statistics Agency, is employed in this investigation, utilizing a documentary study method centered on the Gross Regional Domestic Product (GRDP) at Constant Basic Prices categorized by Field of Business in Sleman Regency and Yogyakarta Special Region Province for the years 2018-2022. The sample comprises 17 economic sectors contributing to the composition of the Gross Regional Domestic Product (GRDP) in Sleman Regency and Yogyakarta Special Region Province. To analyze the preeminent sectors, the research employs the Location Quotient, Shift Share, and Klassen Typology calculation approaches. The findings reveal that the leading sectors in Sleman Regency encompass the Manufacturing Industry, Real Estate, Corporate Services, and Educational Services sectors.